Adaptación y comportamiento agronómico de dos variedades de acelga (Beta vulgaris), sembradas mediante sistema hidropónico de raíz flotante, en la zona de Babahoyo - Ube Troya, Richard Javier (2014)
The planting, production and marketing of chard (Beta vulgaris L) is an economic potential that has not yet been exploited in our country. The crop for domestic and foreign markets , is attractive in the future could become an export product as its features and property development opportunities in this field, and this research will help to have a broader view on this crop (Beta vulgaris L ) , which may undertake programs which facilitate and support the cultivation and marketing of chard . The objective of this research was to evaluate the agronomic performance of the crop of spinach using hydroponic systems. The work was done on the grounds of the experimental farm "San Pablo", located on 7.5 km of track Babahoyo-Montalvo. Eight treatments with 3 replications were investigated. Sowing was done with chard seeds chard Fordhook Giant and Bali, in containers of 1 m2. Treatments were arranged in a randomized complete design blocks. For the evaluation of the average Tukey test at 5 % significance was used. At the end of the crop cycle were evaluated: plant height, number of leaves, root length, root weight, leaf length and yield per square meter..........